QUANTITATIVE EVALUATION OF BIOACCUMULATING TOXIC AND ESSENTIAL METALS IN VEGETABLES PROCURED FROM LOCAL MARKETS OF PAKISTAN AND THEIR PUBLIC HEALTH RISK ASSESSMENT - H. Bano1; A. Mahmood; F. Zafar (Journal of Animal and Plant Sciences, 2016)
Heavy metals uptake were determined in eleven vegetables procured from local market of Karachi and Lahore while results were compared with permissible safe limits set by WHO, SEPA (China) and FSSA (India) to ascertain their public dietary exposure and health hazards. Important findings included: Average concentrations of Pb were exceeding permissible level of WHO and FSSA in onion procured from Karachi and in carrot, potato, bitter gourd and apple gourd from Lahore. Although Cd metal was more accumulated than safe limits set by SEPA in most of vegetable samples from Karachi however it was within permissible range in all vegetables from Lahore. Moreover, average quantity of Zn were exceeded than FSSA set values in onion, bell pepper, ridge gourd, bitter gourd and apple gourd from Karachi as well as in onion, bell pepper, cucumber, taro, carrot and apple gourd from Lahore whereas amount of Fe and Mn metals were found well within safe control of WHO standards in all vegetables from both cities. Daily Intake of Fe and Mn metals were yielded within safe range of reference oral dose values but exceeded in case of Pb, Cd and Zn metals. Calculated Health Risk Index values were found more than one (>1) for Pb, Cd and Zn metals while less than one (<1) for Fe and Mn metals.
Keywords: Heavy metals; Vegetables and Health Risk Index